Diabetes mellitus and comorbid depression: improvement of both diseases with milnacipran. A replication study (results of the Austrian Major Depression Diabetes Mellitus study group) - Abrahamian H (Dove Medical Press, 2012)
Heidemarie Abrahamian,1 Peter Hofmann,2 Johann Kinzl,4 Hermann Toplak31Department of Internal Medicine, Otto Wagner Hospital, Vienna, Austria; 2Department of Psychiatry, 3Department of Internal Medicine, University Hospital, Graz, Austria; 4Department of Psychosomatic Medicine, University Hospital, Innsbruck, AustriaAbstract: Co-morbid depression is common in patients with type 2 diabetes mellitus and is associated with greater mortality risk and a higher incidence of diabetic complications and decreased quality of life. In an earlier pilot study, we found that treatment with the serotonin norepinephrine reuptake inhibitor antidepressant, milnacipran, significantly improved metabolic parameters in diabetic patients with comorbid depression who had an antidepressant response. We sought to replicate these results in a larger cohort (n = 135). Patients received milnacipran and metformin for 6 months and metabolic parameters and depressive symptoms were measured at baseline and after 3 and 6 months. At the end of the study, 72.6% of patients had an antidepressant response (≥50% reduction of baseline Beck Depression Inventory score). Overall, there was significant improvement in the metabolic and anthropometric parameters measured. The number of patients with glycated hemoglobin > 8% (>63.9 mmol/mol), an indicator of poor metabolic control requiring intensive therapeutic intervention, decreased from 31.9% at baseline to 11.9% during the study. As found in the pilot study, levels of total cholesterol and triglycerides were only significantly decreased in antidepressant responders. Body weight was significantly reduced in both responders and non-responders but the effect size was significantly greater in the responder group. In contrast to the pilot study, fasting blood glucose and glycated hemoglobin were significantly decreased to a similar extent in both antidepressant-responders and nonresponders. The present study thus replicates some of the original findings. The main difference between the present and the pilot study is that in the larger cohort significant reductions in fasting blood glucose and glycated hemoglobin were found in all patients irrespective of whether or not they responded to antidepressant treatment. The present data underline the importance of diagnosis and treatment of comorbid depression in patients with type 2 diabetes mellitus with milnacipran.Keywords: depression, diabetes, milnacipran, metabolic control, metformin